Upaya Guru Dalam Peningkatan Kualitas Pembelajaran Sejarah Kebudayaan Islam Kelas X Di Madrasah Abadiyah Gabus - Subchanifa, Dian Pujiatma Vera; Anshory, Anas; Fitri, Nafisah Rahmatul; Mutafida, Alfita Amalia (AL-BURHAN, 2024)
Teacher effort is an effort made by the teacher to solve a problem so that the goals and objectives of the educational institution can be achieved. . Learning quality can be said to be a description of the good or bad results and understanding achieved by students after learning activities are carried out. History of Islamic Culture as one of the compulsory subjects in Madrasas. Researchers conducted research on teachers' efforts to improve the quality of learning the History of Islamic Culture at Madrasah Aliyah Abadiyah Gabus. Data collection in this research is observation, interviews and documentation. Data analysis was carried out by first focusing on the data, then presenting it in descriptive text, and conclusions were drawn by explaining it descriptively. The results of the research show that the efforts made by Islamic Cultural History teachers to improve the quality of Islamic Cultural History learning are quite good. This can be proven based on the efforts that Islamic Cultural History teachers have made to improve the quality of learning.Keywords: Teacher efforts, improving the quality of learning